2006
DOI: 10.1038/modpathol.3800677
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin V somatic hypermutation in mantle cell lymphoma: mutated genotype correlates with better clinical outcome

Abstract: Mantle cell lymphoma is an aggressive B-cell lymphoma for which the biology is incompletely understood. Previous studies have reported that somatic hypermutation of the variable region of the immunoglobulin heavy chain gene (V H ), as commonly defined as o98% homology, can be detected in approximately one-third of mantle cell lymphoma, although the V H mutation status has not been found to significantly correlate with patient survival. In this study, we assessed V H mutation in 55 mantle cell lymphomas using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
2
21
2
Order By: Relevance
“…They also suggest that NF-κΒ and STAT3 pathways may cooperate to play an important role in MCL proliferation, as described in diffuse large B-cell lymphoma. Some studies identified IGHV mutational status as a relevant prognostic factor in MCL, 3,[26][27][28] suggesting an involvement of antigen stimulation in the course of the disease. In these studies, patients with mutated IGHV appeared to have a better clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…They also suggest that NF-κΒ and STAT3 pathways may cooperate to play an important role in MCL proliferation, as described in diffuse large B-cell lymphoma. Some studies identified IGHV mutational status as a relevant prognostic factor in MCL, 3,[26][27][28] suggesting an involvement of antigen stimulation in the course of the disease. In these studies, patients with mutated IGHV appeared to have a better clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] However, unlike in chronic lymphocytic leukemia, in MCL the variable heavy chain gene (VH) mutation status shows no association with ZAP-70 expression and its prognostic relevance is the subject of heated debate. [6][7][8] Additional genetic alterations that occur in subsets of MCL appear to disturb the cell cycle machinery and to interfere with cellular responses to DNA damage. In particular, cyclin D1 upregulation, genomic amplification of cyclin-dependent kinase 4 (CDK4), deletions of the CDK inhibitor p16INK4a, and overexpression of BMI-1, a transcriptional repressor of the p16INK4a locus, are associated with deregulation of cell cycling in MCL.…”
Section: Introductionmentioning
confidence: 99%
“…8 Besides the biological relevance of SHM, there is a broad base of evidence to suggest that IgVH SHM is a clinically significant phenomenon in various types of B-cell lymphoma, as demonstrated by studies reporting that cases of hypermutated CLL 9 and splenic marginal zone lymphoma (SMZL) have a better prognosis, 10 while cases of hypermutated mantle cell lymphoma (MCL) display specific clinicopathological features (leukemic course, longer survival). [11][12][13][14] There were two aims of the current study. First, we wished to identify a set of markers that could be analyzed by immunohistochemical assays, since this could have a potential clinical value for analyzing SHM status.…”
Section: Introductionmentioning
confidence: 99%
“…The study focuses on small B-cell lymphomas in which the presence of Ig somatic hypermutation has been reported to be a biological variable of clinical significance, such as CLL, MCL and SMZL, as noted above. [9][10][11][12][13][14] Furthermore, expression profiling was used in patients' samples to identify genes that may play a role in the process of SHM.…”
Section: Introductionmentioning
confidence: 99%